2006
DOI: 10.1897/05-600r.1
|View full text |Cite
|
Sign up to set email alerts
|

Contamination by polybrominated diphenyl ethers and persistent organochlorines in catfish and feed from Mekong River Delta, Vietnam

Abstract: Commercial feeds for aquaculture and catfish samples were collected from the Mekong River Delta, Vietnam, for determination of polybrominated diphenyl ethers (PBDEs) and selected persistent organochlorines, including polychlorinated biphenyls (PCBs), DDT and its metabolites (DDTs), chlordane-related compounds (CHLs), hexachlorocyclohexane isomers (HCHs), and hexachlorobenzene (HCB). The most abundant contaminants were DDTs, with concentrations ranging from 10 to 700 ng/g lipid weight, followed by PCBs (1.0-80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 35 publications
3
21
1
1
Order By: Relevance
“…Concentrations of PHCs in certain species, such as crimson snapper (Lutjanus erythopterus) and snubnose pompano (Trachinotus blochii), were at high enough concentrations to cause human health concerns . Furthermore, recent and previous studies found that PHCs, especially DDTs, were ubiquitous in fish feed including compound feed and trash fish (Hites et al, 2004;Minh et al, 2006;Guo et al, 2009b). These studies speculated that the presence of PHCs in farmed fish may be mainly derived from fish feed.…”
Section: Introductionmentioning
confidence: 96%
“…Concentrations of PHCs in certain species, such as crimson snapper (Lutjanus erythopterus) and snubnose pompano (Trachinotus blochii), were at high enough concentrations to cause human health concerns . Furthermore, recent and previous studies found that PHCs, especially DDTs, were ubiquitous in fish feed including compound feed and trash fish (Hites et al, 2004;Minh et al, 2006;Guo et al, 2009b). These studies speculated that the presence of PHCs in farmed fish may be mainly derived from fish feed.…”
Section: Introductionmentioning
confidence: 96%
“…Disposal consumer products in landfill sites in Vietnam were suggested to contain higher octa-BDE content (Eguchi et al 2013). A similar result was observed in fish samples collected near open dumping sites in Can Tho, Mekong River Region, showing marked differences in accumulation patterns between dumping site fish and farmed fish (Minh et al 2006). The above Pearson analysis was performed to assess the correlation between individual PBDE congeners in sediment samples, and the results are shown in Table 3.…”
Section: Pbde Congener Profiles In Sediment Samplesmentioning
confidence: 55%
“…Investigations on PBDEs in Vietnam are scarce and limited to a few cities and industrial areas (Minh et al 2006;Minh et al 2010;Tue et al 2010;Hien et al 2012;Romano et al 2013;Tue et al 2013). The level of PBDEs in environmental media such as indoor dust and air in some e-waste recycling sites in Hung Yen Province or Hai Phong City was significantly higher than reference sites in Hanoi .…”
Section: Introductionmentioning
confidence: 99%
“…Human contact with fish pond water occurs during fish harvesting and cyclic flooding episodes contribute to the contamination of ambient waters with human and animal excreta (Hau et al 1999). A study by Lan et al Several studies have shown water-borne disease transmission (Corwin et al 1996;Hau et al 1999) and chemical water pollution by pesticides (Minh et al 2006;Minh et al 2007) in the region. Surprisingly, polluted water is frequently utilized for personal hygiene such as showering or bathing either in the river (44%) or in a bathroom (86%) supplied with river water.…”
Section: Local Perception Of Sanitation and Hygienementioning
confidence: 99%